A systematic literature review and bibliometric analysis of eco‐innovation on financial performance: Identifying barriers and drivers - López Pérez, Germán; García Sánchez, Isabel María; Zafra Gómez, José Luis (Business strategy and the environment, 2024)
Eco‐innovation strategies are essential elements for companies developing core competencies in the circular economy model. The academic world has begun to study the knowledge of these business decisions, and there is incipient literature on the subject. In this context, this paper aims to contribute to the current knowledge on the impact of eco‐innovation strategies on corporate performance by exposing and synthesizing the distinct positions found in the literature. For this purpose, a systematic and bibliometric review of 81 articles related to the economic impact of eco‐innovation on firm performance, as well as the barriers and drivers of these strategies, was carried out. After analyzing the several types of eco‐innovation, our results show that although previous empirical evidence suggests the existence of a positive effect, it is not generalizable due to the existence of several factors that may condition the impact of eco‐innovation on corporate performance and its implementation. This study delves into the current academic literature on eco‐innovation and firm performance, determining that both size and the environment in which a company is framed constitute a series of conditioning factors that may clarify why there is no consensus in the academic literature in this regard. In addition, this work encourages future lines of research with the aim of shedding light on this field of knowledge.